2017
DOI: 10.12659/msm.903272
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Uncovers Molecular Mechanisms Underlying Pathological Complete Response to Chemotherapy in Patients with Operable Breast Cancer

Abstract: BackgroundThis study aimed to identify key genes contributing to pathological complete response (pCR) to chemotherapy by mRNA sequencing (RNA-seq).Material/MethodsRNA was extracted from the frozen biopsy tissue of patients with pathological complete response and patients with non-pathological complete response. Sequencing was performed on the HiSeq2000 platform. Differentially expressed genes (DEGs) were identified between the pCR group and non-pCR (NpCR) group. Pathway enrichment analysis of DEGs was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…As one of the most common pathways of malignancies, the pathway of ‘Neuroactive ligand-receptor interaction’ ranks fifth in genes with mutation in the central nervous system (61). A previous study reported that low expression of cannabinoid receptor-1 (CNR1), part of the neuroactive ligand-receptor interaction pathway, indicated that breast cancer patients may benefit from chemotherapy (62). Notably, this CNR1 was among the 1,237 DEGs following cinobufotalin treatment in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the most common pathways of malignancies, the pathway of ‘Neuroactive ligand-receptor interaction’ ranks fifth in genes with mutation in the central nervous system (61). A previous study reported that low expression of cannabinoid receptor-1 (CNR1), part of the neuroactive ligand-receptor interaction pathway, indicated that breast cancer patients may benefit from chemotherapy (62). Notably, this CNR1 was among the 1,237 DEGs following cinobufotalin treatment in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this CNR1 was among the 1,237 DEGs following cinobufotalin treatment in breast cancer cells. In addition, this pathway was reported to serve a vital role in tumorigenesis and chemotherapy for breast cancer (62,63), which suggested that cinobufotalin may exhibit its curative potential for breast cancer by influencing the neuroactive ligand-receptor interaction pathway. The co-treatment of cinobufotalin to chemotherapeutics may induce a synergistic effect by suppressing the neuroactive ligand-receptor interaction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…VAX2 is found to be a transcription factor that regulates 3 genes ( PLCB4 , ADCY6 , and CNR1 ) in RNA tissue in response to chemotherapy in patients with operable breast cancer. 24…”
Section: Biological Insightmentioning
confidence: 99%
“…VAX2 is found to be a transcription factor that regulates 3 genes (PLCB4, ADCY6, and CNR1) in RNA tissue in response to chemotherapy in patients with operable breast cancer. 24 MAF1 displays tumor suppressor activity. Surprisingly, blocking the synthesis of ribosomal RNA and transfer RNAs is insufficient to account for MAF1's tumor suppressor function.…”
Section: Biological Insightmentioning
confidence: 99%
“…Oxidative phosphorylation was found to be a crucial pathway in cancer progression 26,27 (Figure S1). Meanwhile, we found that these dysregulated peptides are involved in retrograde endocannabinoid signaling which have been proved to play an important role in multiple cancer progression [28][29][30] (Figure S2). These results showed that the dysregulated peptides might play an important role in BC.…”
mentioning
confidence: 99%